Agama Dan Sekularisasi Pada Masyarakat Moderen - Rosana, Ellya (Universitas Islam Negeri Raden Intan Lampung, 2018)
Religion in general can be interpreted as a belief system and religious practices based on some sacred and supernatural values that direct human behavior, give meaning to life, and unite followers into a moral community. Although it cannot be denied that all religions of various kinds and forms today have developed. Religion is also believed not only to talk about rituals but also to talk about values that must be concretized in social life, including in the realm of constitution, the demand that religious values be applied in the life of the state. Each believer believes that the teachings and values he adheres to must be upheld in the life of society and the state. The emergence of the demands of the concretization of religious values in the life of the state that led to a debate that has not been completed regarding the relations between the state and religion, including secularism that separates religion and state even though in secular society religion is not rejected at all, but religion must adjust the will of society .